The Benelux approach to EU integration and external action. Issue 3 (27th May 2017) - Blockmans, Steven
ABSTRACT: As small states with a cosmopolitan outlook, Belgium, the Netherlands and Luxembourg, have a natural interest in good-neighbourly relations and in cooperating through the EU. However, despite the closely knit nature of the economic, monetary and physical spheres of the lowlands, their attitudes to European integration diverge. Whereas the Netherlands has taken a transactional and even Eurosceptic position, Belgium sticks to its federalist approach to integration as a natural extension of its own constitutional structures which receive shelter from the EU. Luxembourg shares the federalist ideals but adopts an autonomous stance to protect its position as an international tax haven. These generic findings apply less to matters of EU foreign and security policy, which is the main subject of investigation of this special forum.